Comparison of Tobacco Control Programs Worldwide: A Quantitative Analysis of the 2015 World Health Organization MPOWER Report - Heydari, Gholamreza (Int J Prev Med, 2016)
BACKGROUND: A report of the activities of countries worldwide for six main policies to control tobacco use is published once every 2 years by the World Health Organization (WHO). Our objective was to perform a quantitative analysis for it in countries and regions to make a simple view of its programs. METHODS: This was a cross-sectional study by filling out a validated checklist from the 2015 WHO Report (MPOWER). All ten MPOWER measures got scores and were entered independently by two individuals and a third party compared the values. RESULTS: Fifteen countries, which acquired the highest scores (85% of total 37), included Panama and Turkey with 35, Brazil and Uruguay with 34, Ireland, United Kingdom, Iran, Brunei, Argentina, and Costa Rica with 33, and Australia, Nepal, Thailand, Canada, and Mauritius with 32 points. CONCLUSIONS: Comparison of scores of different countries in this respect can be beneficial since it creates a challenge for the health policymakers to find weakness of the tobacco control programs to work on it.